PENGARUH PENGGUNAAN MEDIA BERBASIS HIPERTEXT PADA MATERI POKOK STRUKTUR ATOM DAN TABEL PERIODIK TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 3 MAKASSAR - Ahmad, Fandi (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2014)
This research is a quasi experiment that aims to determine the effect the use of hypertext-based  as media on  atomic structure and periodic table to the study results of the students Class X of  SMAN 3  Makassar  with  "pre and post-test control group design." The population for this study is the students class X  SMAN  3   Makassar, that consists of nine classes and the samples consits of two that a class  experiment X2 and X3 class as a control group that created by random sampling method. Variables consisted of free variables by using media-based learning hipertext. while the dependent variable is learning of student result. The  data was collected by pretest and posttest. Data were analyzed by descriptive  and inferential statistics with SPSS (Statistial Package for Social Science) for Windows version 16. The results showed the average value of experimental pretest was 21.88 with a standard deviation of 8.21 and the average posttest value was 73.59 with a standard deviation of 10.15. While the control class average pretest value was 22.50 with a standard deviation of 8.80 and the average value posttest was 65.88 with a standard deviation of 10.17. ANACOVA test results, obtained significance value of p = 0.000 <α = 0.05, This means that Ho is rejected and the HI is received, the hypertext-based as media on  Atomic Structure and Periodic Table influence on students result learning at class X SMAN 3 Makassar.